Improving Learning Outcomes in Short-Distance Running Through a Play-Based Approach for Grade V Students - Aji, Bayu Purnomo; Wismanadi, Himawan (Universitas Pendidikan Indonesia, 2023)
Sprinting requires one aspect of fitness, namely speed, which serves to support the body's ability to perform the same and repeated movements in a short time. This study aims to determine the level of effectiveness in improving the learning outcomes of 30-meter short-distance running using a play-based approach. The method used is action research, conducted in two cycles. The subjects of this study were 35 fifth-grade students from SD Negeri Manukan Wetan IV Surabaya, consisting of 13 boys and 22 girls. The study utilized pre-test and post-test data collection techniques. Before the implementation of action research, the students had an average completion score of 36 for short-distance running. This score increased to 45.71 in cycle I. In cycle II, the initial student score of 58.29 improved to 90.29, with 4 students failing to complete the test. Therefore, it can be concluded that the play-based approach has proven effective in enhancing the learning outcomes of 30-meter short-distance running for fifth-grade students at SD Negeri Manukan Wetan IV Surabaya for the 2022/2023 school year.